Pernikahan Childfree Perspektif MUI Kota Padangsidimpuan - H, kurniawan; Ahmatnijar, Ahmatnijar; Sirait, Adi Syahputra (UIN Syekh Ali Hasan Ahmad Addary Padangsidimpuan, 2023)
This research examines voluntary childfree marriages or childfree marriages from the perspective of the Indonesian Ulema Council, Padangsidimpuan City. This research is a field research with a qualitative approach from the perspective of Maqasid Al-Syariah. The data sources in this study consisted of two sources of data, namely primary data which was obtained directly from the Chairman of the Padangsidimpuan MUI and the Chair of the Fatwa Commission and the Secretary of the Padangsidimpuan MUI Fatwa Commission, and secondary data collected through references available in various places that are considered relevant to discussing childfree, the data collection techniques used are interviews and documentation. The data analysis technique used by researchers in this study is inductive qualitative. The results of the study, namely the Indonesian Ulema Council of the Padangsidimpuan City MUI explained that childfree marriage or marriage with a commitment without children between husband and wife is something that violates the Shari'a if it is carried out without any harm between the two parties in accordance with the Word of Allah SWT in the Qur'an sura Al-Baqarah: 223 concerning the obligations and rewards of having children, and also in his perspective the Padangsidimpuan City MUI emphasizes the role of children in marriage which is very central between husband and wife in protecting offspring (Hifz al-Nasb) in Maqasid Al-Syariah both in religious and cultural factors that exist in Indonesia, so there is no reason that allows someone to deliberately not have children except in circumstances that are harmful and in accordance with Islamic religious law.